Predictors of Mortality From a Population-Based Cancer Registry Data in Jos, Nigeria: A Resource-Limited Setting - Silas, Olugbenga Akindele; Musa, Jonah; Afolaranmi, Tolulope Olumide; Sagay, Atiene Solomon; Evans, Charlesnika Tyon; Achenbach, Chad J.; Hou, Lifang; Murphy, Robert Leo (Frontiers in Medicine, 2020)
Background It is a well-documented fact that world-wide cancer incidence and mortality remains high in Human Immunodeficiency Virus (HIV) infected population despite potent antiretroviral therapy. With the current capture of HIV status of cancer patients in our cancer registry at Jos Nigeria, this study aims to assess the effect of HIV on cancer mortality outcomes. Methodology We conducted a 2-year retrospective cohort study of cancer registry data from Jos, north central Nigeria. The cancers were grouped into cervical, breast, liver, hematologic, colonic, prostate and others in this study. Patients were followed up to determine their patient time contribution from time at initiation of cancer treatment to death or the end of study period. Those lost to follow-up were censored at date of their last known follow-up in clinic. Results Out of 930 cancer cases evaluated, 52(5.6%) were HIV positive, 507(54.5%) were HIV negative and 371(39.9%) did not know their HIV status. After 525,223 person- days of follow-up, there were 225 deaths leading to a crude mortality rate of 4.3 per 10,000 person-days. Median survival probability for both HIV-infected and HIV uninfected patients were equal ( 1,013 days).Unadjusted hazard of death was associated with marital status, HR 0.57(95% CI: 0.41, 0.79,p = 0.001); greater age, HR 0.99(95% CI: 0.98,0.99,p = 0.002); hepatitis virus, HR 2.40(95% CI: 1.69,3.43,p= 0.001); breast cancer, HR 0.47(95% CI: 0.31,0.69,p= 0.001); liver cancer, HR 1.97(95% CI:1.38,2.80,p= 0.001); prostate cancer, HR 0.15 (95% CI: 0.08,0.28,P= 0.001) . In an adjusted model, only liver cancer AHR 3.22(95% CI: 1.44, 7.22, p= 0.005) remained significantly associated with death regardless of HIV status. Conclusion Mortality following liver cancer is three times more than other cancers regardless of HIV status. Linkage of HIV and cancer data especially in regions with high HIV prevalence should be advocated to better understand the role of HIV on cancer indices.